임상치과위생사의 직무배태성에 영향을 미치는 요인 - 김영임; Im-young Kim; 장윤정; Yun-jung Jang (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: This study aimed to provide basic data to establish a foundation for efficient operation of the organization by identifying the factors that affect the job embeddedness of dental hygienists. Methods: A survey was conducted from March to July 2018, targeting dental hygienists working in dental clinics and hospitals. Results: The study of the factors affecting job embeddedness of dental hygienists revealed that along with career, marital status, surface acting of emotional labor, and even emotional hiding and false expression, which are sub-areas of the surface acting, have statistically significant influences on job embeddedness. In other words, in a married dental hygienist with relatively high work experience, the surface acting of emotional labor is found to be high in job embeddedness, and the explanatory power of the model is approximately 53.2%. Conclusions: In order to improve the job embeddedness of clinical dental hygienists, it seems necessary to prepare an effective program to strengthen the surface behavior of emotional labor.